Pra Analisis Forensic Microbial Profiling Melalui Isolasi Bakteri Endofit Khas Datura metel L. - Husein, Saddam; Virginia, Diva Arsynta; Nofita (Chemistry Department, Universitas Islam Indonesia, 2026)
This study aimed to isolate and characterize endophytic bacteria from young leaves of Datura metel L. as a preliminary step in forensic microbial profiling. Endophytic bacteria are non-pathogenic microorganisms that inhabit plant tissues and have the potential to produce bioactive compounds. This research employed a laboratory experimental method with a descriptive approach through isolation using Nutrient Agar (NA) medium, followed by purification using repeated streaking and macroscopic observation of colony morphology. Leaf samples were divided into leaf petiole (TD), leaf stem (BD), veined leaf (DT), and veinless leaf (D). The results showed that isolates I-TD and I-DT exhibited colony growth characterized by circular shape, white to yellowish-white color, smooth to slightly mucoid surface, and entire margins. In contrast, isolates I-BD and I-D showed no colony growth. Purification was successfully achieved in isolates I-TD and I-DT, while the others could not be purified. These findings indicate that the distribution of endophytic bacteria in Datura metel leaves is uneven, with leaf petioles and veined leaves having greater potential as sources of endophytic isolates.